Skid resistance performance enhancement using different macrotexture parameters in chip seal - Then, Kang Jin (2017)
Transportation plays an important role to a country economic growth. As transportation is convenient to other economic activities such as construction industry and tourism, grows in other sectors will significantly affecting transportation industry as well. As a result of this situation, steady increases in the number of road crashes in every year from year 1997 to 2015 have been recorded. Skidding has been determined as one of the main causes of crash hence making an effort to determine the macrotexture characteristics of road pavements which include mean texture depth (MTD) and British Pendulum Number (BPN) is crucial. 21 numbers of asphalt concrete pavement samples were prepared for the purpose of laboratory works. Volumetric patch method and British pendulum test were used to examine MTD and BPN. The MTD results recorded from this research varied from 1.53 mm to 2.39 mm while the BPN obtained were varied from 57.7 to 114.5. MTD of 2.20 mm has been identified as the optimum skid resistance performance in this research. The value of correlation coefficient, R between MTD and BPN was 0.4748 showing that there was both parameters were positively correlated.